The Illustrated Glossary of Paper Conservation: a tool for interacting cultures - Almada, Márcia; Bojanoski, Silvana; Zervos, Spiros (Journal of Integrated Information Management, 2023)
In 2021, the "Illustrated Glossary of Paper Conservation: Damages and Treatments" was published digitally in Portuguese, Spanish, English, and Greek. The authors, Márcia Almada and Silvana Bojanoski, are university professors of professional training courses in paper conservation at Brazilian universities. The idea of publishing an illustrated glossary arose from the need to create a guide that could standardise discourse in a field that still lacks systematic terminology. The four languages were chosen due to academic and professional partnerships established between the authors and collaborators and aim to expand and strengthen interactions among diverse cultures and to facilitate technical communication. The Portuguese version is based on the Brazilian experience; the English version was developed following the terminology used by the American Institute of Conservation and served as a point of convergence for resolving conflicts during translation; the Spanish version was constructed by professionals at the National Library of Mexico, and the Greek version draws on the experience of the Department of Archival, Library & Information Studies, University of West Attica.